(3YbhO GddBd aj GdehTMGJ hGdCRLGds - (3eMeO Hf MSf Hf Ydj Hf YKeGf GdfhGLj GdTGaYj , TeS GdOjf,J (B859 (3g` s ((3eMeO Hf eSde s)
(3ChdgG (B:s
(3abO LeYJ gPg GdMOjbI aj GdehTMGJ hGdCRLGd ebJUQkG Ydi eG hbY dj aj Pdc ef GdfhYjf, eQJHkG dg Ydi HGHjf GdHGH GdChd(B: (3aj GdehTMGJ s
(3BNQgG (B:s
(3bdJ(B: (3JUjQ ddbeQI GdLjg bGd dj(B: (3JWdH beQ hhLgj beQ s
(3fbdgG Yf fSNI GdeUfa HNWgs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B88 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B9 - (3U (B203 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B2 - (3U (B200s
(3EjVGM Gdecfhf ddHZOGOi(B: (3L (B2 - (3U (B114 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B5 - (3U (B46 s
Keywords: (3GdCOHs